ANALISIS PERBEDAAN MODE ANTARA EXTRACTION DAN FULL CONDENSING TERHADAP EFISIENSI TURBIN UAP KAPASITAS 22 MW - Mirza Ramadhani (2021)
The steam turbine is one of the important components in supporting a power plant. Steam turbine generator (STG) operations at PT. XYZ have been carried out continuously since 1992. Each STG at PT. XYZ has a capacity of 22 MW based on the initial design in the manual book and is divided into two modes. During its 28 years of operation, it is estimated that STG's performance has decreased due to several factors such as increased vibration, increased pressure drop for each stage, increased steam inflow rate at normal load, and increased exhaust temperature. Therefore it is necessary to analyze the efficiency of STG whether the efficiency and performance are still in a reliable condition or not. Based on the results of the analysis of the five existing STGs by taking samples on January 13, 2020 and using the Rankine cycle calculation method, it was found that the full condensing mode was at STG 51-G-101 A / B / E with an efficiency of 80.18% each, 66.25%, and 76.75%. The extraction mode is at STG 51-G-101 C / D with efficiency values of 74.85% and 74.66%. This actual calculation has decreased compared to the design calculation by 85%, but STG's performance is still in good condition but must be monitored.